Effect of Sm and Mn Co-doping on the Crystal Structure and Magnetic Properties of \(BiFeO_3\) Polycrystalline Ceramics - Nguyen Van, Hao; Pham Van, Hai; Truong Thi, Thao; Nguyen Thi Minh, Hong; Pham Truong, Tho (Communications in Physics, 2020)
The crystal structure, phonon vibration, microstructure, and magnetic properties have been investigated in multiferroics Bi0.9Sm0.1Fe1-xMnxO3 for \(x = 0.02 – 0.1\). The structural analysis by XRD and Rietveld refinement suggest that Mn doping compounds crystallize in the polar R3c rhombohedral symmetry (isostructural with BiFeO3). Raman analysis confirms no structural transformation but the change of line widths and peak intensities reveal the lattice distortion in Mn-substitution samples. The study of microstructure shows no obvious change of grain size and shape. The magnetic properties of the as-prepared samples show the linear magnetic field dependence of magnetization, suggesting the antiferromagnetic feature of polycrystalline ceramics. The field dependence of magnetization measured after two-years synthesis and after applying an electric field reveal a decrease of maximum magnetization but the hysteresis loops retain the antiferromagnetic behavior. The implication of these results is that the magnetic properties of single structural phase compound, including coercivity and remanent magnetization, do not show the aging behavior as observed in the morphotropic phase boundary systems